2016
DOI: 10.1186/s40689-016-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale zero-valent iron-impregnated agricultural waste as an effective biosorbent for the removal of heavy metal ions from wastewater

Abstract: A novel, nanoscale zero-valent iron-impregnated cashew nut shell (NZVI-CNS) was synthesized towards the removal of Ni(II) ions from aqueous solution using impregnation procedure. The factors affecting Ni(II) ion adsorption in a batch mode were studied including the initial metal ion concentration, solution pH, temperature, adsorbent dosage, and contact time. The adsorption isotherm and kinetics could be described well with Freundlich and pseudo firstorder, respectively. The maximum monolayer adsorption capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…At last, ferrous ion was impregnated on to the RSS. The reduction of ferrous ion to ZVI was explained by the following equation [35]: 2 normalFe false( aq false) 2 + + normalBH 4 false( aq false) + 2 normalH 2 O + support false→ 2 F normale normalo suppor normalt false( s false) + BO 2 ( normalaq ) + 4 H ( normalaq ) + + 2 H 2 ( normalg )…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At last, ferrous ion was impregnated on to the RSS. The reduction of ferrous ion to ZVI was explained by the following equation [35]: 2 normalFe false( aq false) 2 + + normalBH 4 false( aq false) + 2 normalH 2 O + support false→ 2 F normale normalo suppor normalt false( s false) + BO 2 ( normalaq ) + 4 H ( normalaq ) + + 2 H 2 ( normalg )…”
Section: Methodsmentioning
confidence: 99%
“…At last, ferrous ion was impregnated on to the RSS. The reduction of ferrous ion to ZVI was explained by the following equation [35]:…”
Section: Nzvi-rss Preparation and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Nickel (Ni) ions can trigger severe health problems, that is, renal disturbances, allergies, infertility, lung cancer, hepatitis, dermatitis, gingivitis, insomnia, nausea, and stomatitis. [ 7 ] Cadmium (Cd) is the most toxic pollutant which can damage lungs, kidneys, and liver. [ 8 ] Similarly, cobalt (Co), copper (Cu), manganese (Mn), iron (Fe), selenium (Se), zinc (Zn), and strontium (Sr) are directly considered to be toxic to biota when present is excessive quantities in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nano zero-valent ironimpregnated (NZVI) has several advantageous with respect to removal of heavy metal from wastewater such as extreme removal capacity, large surface area, high reactivity and easy solid-liquid separation [28][29][30][31][32]. Recent investigations indicated that NZVI can be supported by surface stabilisers like polyvinyl alcohol [33], resin [34], activated carbon fibre [35], Chitosan [36], orange peelpith [29], pumice [32], cashew nut shell (CNS) [37,38] etc., to enhance their stability and dispersibility.…”
Section: Introductionmentioning
confidence: 99%